2013
DOI: 10.1094/pdis-01-13-0075-re
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects ofSquash vein yellowing virusInfection on Watermelon

Abstract: Adkins, S., McCollum, T. , W. W. 2013. Physiological effects of Squash vein yellowing virus infection on watermelon. Plant Dis. 97:1137-1148.Squash vein yellowing virus (SqVYV) is the cause of viral watermelon vine decline. The virus is whitefly-transmitted, induces a systemic wilt of watermelon plants, and causes necrosis and discoloration of the fruit rind. In the field, SqVYV is often detected in watermelon in mixed infections with other viruses including the aphid-transmitted Papaya ringspot virus type W (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…The lack of reported SqVYV detection in Cucurbita maxima may be due to the lack of symptoms in fruits (with no rind necrosis in either greenhouse or field grown plants) and decline symptoms being delayed compared to watermelon. Early infection of young Cucurbita maxima plants could be more serious, as suggested by the decline of young plants in our greenhouse studies, although SqVYV-induced decline of young watermelon plants in commercial fields has not been reported (1). In northern states, cold winters likely limit survival of cucurbit weed or volunteer crop reservoirs for the virus to pass from one growing season to the next.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The lack of reported SqVYV detection in Cucurbita maxima may be due to the lack of symptoms in fruits (with no rind necrosis in either greenhouse or field grown plants) and decline symptoms being delayed compared to watermelon. Early infection of young Cucurbita maxima plants could be more serious, as suggested by the decline of young plants in our greenhouse studies, although SqVYV-induced decline of young watermelon plants in commercial fields has not been reported (1). In northern states, cold winters likely limit survival of cucurbit weed or volunteer crop reservoirs for the virus to pass from one growing season to the next.…”
Section: Discussionmentioning
confidence: 61%
“…To examine the response to SqVYV inoculation of mature plants bearing fruit, 21 vining cucurbits in 12 species were vertically trellised on soft cotton strings to allow production of larger plants with fruit, more typical of field grown plants as described elsewhere (1). Cucurbits were selected to represent crop and weed species, and the diversity of symptoms observed in the initial experiments on young plants without fruit.…”
Section: Methodsmentioning
confidence: 99%
“…Little is known about the effects of virus infection on nutrient uptake, distribution and accumulation in plant tissues, although mineral nutrition plays an important role in plant-pathogen interactions (Datnoff et al, 2007;Huber et al, 2012) and in disease control practices (Dordas, 2008;Gupta et al, 2017). Previous work has demonstrated that the presence of virus affected P, Mg, B, Cu, and Mo content in infected leaves (Overholt et al, 2009;Adkins et al, 2013), but the alterations seemed to vary according to the virus considered. In this work, GPGV did not influence the concentrations of B or those of most nutrients.…”
Section: Effect Of B Deficiency and Gpgv Infection On Nutrient Contentsmentioning
confidence: 99%
“…In addition to watermelon, the virus can infect numerous other cucurbit species, including several common cucurbit weeds, some of which serve as reservoirs for SqVYV (4,5,33). Symptoms vary depending on host but, in watermelon, infection by SqVYV results in a rapid collapse of the plant (hence the name watermelon vine decline) that typically occurs as the crop nears harvest (1).…”
mentioning
confidence: 99%